2004
DOI: 10.1002/humu.20010
|View full text |Cite
|
Sign up to set email alerts
|

Leber congenital amaurosis: Comprehensive survey of the genetic heterogeneity, refinement of the clinical definition, and genotype-phenotype correlations as a strategy for molecular diagnosis

Abstract: Communicated by Jean-Claude KaplanLeber congenital amaurosis (LCA) is the earliest and most severe form of all inherited retinal dystrophies, responsible for congenital blindness. Disease-associated mutations have been hitherto reported in seven genes. These genes are all expressed preferentially in the photoreceptor cells or the retinal pigment epithelium but they are involved in strikingly different physiologic pathways resulting in an unforeseeable physiopathologic variety. This wide genetic and physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
271
1
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(287 citation statements)
references
References 38 publications
8
271
1
7
Order By: Relevance
“…It is obvious that there are still unidentified mutations in LCA and further genetic mapping and cloning of new candidate genes are required. 9 In another genetic study, 17 a homozygous nonsense mutation, Trp278X, in the photoreceptor-pineal gene AIPL1 was found in four Pakistani families with LCA. These patients presented with a severe phenotype of LCA with hand motion to no light perception vision and fundus findings ranging from maculopathy to diffuse pigmentary retinopathy.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is obvious that there are still unidentified mutations in LCA and further genetic mapping and cloning of new candidate genes are required. 9 In another genetic study, 17 a homozygous nonsense mutation, Trp278X, in the photoreceptor-pineal gene AIPL1 was found in four Pakistani families with LCA. These patients presented with a severe phenotype of LCA with hand motion to no light perception vision and fundus findings ranging from maculopathy to diffuse pigmentary retinopathy.…”
Section: Discussionmentioning
confidence: 96%
“…In the series of Perrault et al, 16 GUCY2D, RPE65, and CRX genes accounted for 27% of Leber cases. Hanein et al, 9 screened seven LCA causative genes in 179 unrelated LCA cases and found mutations in 47.5% of the patients (GUCY2D (21.2%), CRB1 (10%), RPE65 (6.1%), RPGRIP1 (4.5%), AIPL1 (3.4%), TULP1 (1.7%), and CRX (0.6%)). It is obvious that there are still unidentified mutations in LCA and further genetic mapping and cloning of new candidate genes are required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, 24 pathogenic variants have been described in TULP1, including 12 missense and 12 nonsense or frameshift mutations. [17][18][19][20][21][22][23][24][25][26][27] In all, 10 out of the 12 missense mutations are present in the tubby domain. The two novel missense mutations, R311Q and R342Q, that we have found in this study also affect amino acids of the tubby domain.…”
Section: Mutation Finding In Non-consanguineous Familiesmentioning
confidence: 99%
“…The following genes are known to be associated with LCA: GUCY2D, RPE65, SPATA7, AIPL1, LCA5, RPGRIP1, CRX, CRB1, CEP290, IMPDH1, RD3, RDH12, KCNJ13, LRAT and TULP1. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] It is difficult to estimate the proportion of patients with mutations in the different genes, as some, such as IMPDH1 (LCA11) is considered to be rare, other, as CEP290 accounts for almost 20%, and for some such as TULP1 and LRAT the number is uncertain. One of the most studied LCA genes is CRB1 at 1q31q32.1, which consists of 12 exons and encodes a protein Crumbs homologue that participates in determination and maintenance of photoreceptor architecture.…”
Section: Introductionmentioning
confidence: 99%